RNA-Dependent Regulation of Virulence in Pathogenic Bacteria - Chakravarty, Shubham; Massé, Eric (Frontiers in Cellular and Infection Microbiology, 2019)
During infection, bacterial pathogens successfully sense, respond and adapt to a myriad of harsh environments presented by the mammalian host. This exquisite level of adaptation requires a robust modulation of their physiological and metabolic features. Additionally, virulence determinants, which include host invasion, colonization and survival despite the host’s immune responses and antimicrobial therapy, must be optimally orchestrated by the pathogen at all times during infection. This can only be achieved by tight coordination of gene expression. A large body of evidence implicate the prolific roles played by bacterial regulatory RNAs in mediating gene expression both at the transcriptional and post-transcriptional levels. This review describes mechanistic and regulatory aspects of bacterial regulatory RNAs and highlights how these molecules increase virulence efficiency in human pathogens. As illustrative examples, Staphylococcus aureus, Listeria monocytogenes, the uropathogenic strain of Escherichia coli, Helicobacter pylori and Pseudomonas aeruginosa have been selected.